2011
DOI: 10.1080/19317611.2011.596256
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Parents’ Perspectives on Adolescent Sexuality Education

Abstract: Structural equation modeling was used to examine a model of factors related to Chinese parents" level of involvement in sexuality education for adolescents. Greater parental education was indirectly related to parents" engagement in sexuality education through its relationship with more traditional cultural values, greater perceived knowledge of sexuality, and increased quality of the parent-child relationship. The model was found to be largely consistent regardless of the gender of the parent or child and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…Married gay men were more reluctant to disclose their sexual orientation to heterosexual partners for fear of divorce and subsequently broken family ties[49]. Chinese gay men experience immense pressure, discrimination, which may contribute to greater vulnerability for health issues including HIV[5052]. Despite similar HIV risk trends among gay men worldwide, sociopolitical circumstances in the conservative Chinese cultures often relegates individuals into a space of secrecy and further risk.…”
Section: Discussionmentioning
confidence: 99%
“…Married gay men were more reluctant to disclose their sexual orientation to heterosexual partners for fear of divorce and subsequently broken family ties[49]. Chinese gay men experience immense pressure, discrimination, which may contribute to greater vulnerability for health issues including HIV[5052]. Despite similar HIV risk trends among gay men worldwide, sociopolitical circumstances in the conservative Chinese cultures often relegates individuals into a space of secrecy and further risk.…”
Section: Discussionmentioning
confidence: 99%
“…9 A study conducted in China recorded almost similar findings, where more than half (58.5%) correctly answered the questions on reproductive knowledge and most parents (65.3%) were knowledgeable regarding HIV/AIDS questions. 23 From the current study, most of the respondents showed sufficient knowledge, which indicated that they received good education from their teachers or other sources. Out of 20 questions asked, almost half of the participants answered wrongly only on two items: "The boys reach their puberty as early as the age of 15" and "Chlamydia is a sexually transmissible infection that only affects women."…”
Section: Discussionmentioning
confidence: 62%
“…Thirteen articles from twenty-nine papers reviewed reported parents' perception towards their involvement and their experiences of providing SE at home. According to the analysis, most parents agreed the importance of SE for the well-being of adolescents and displayed high willingness to engage in their adolescents' SE, however, majority of them had not or rarely led discussions related to sexuality knowledge with their children [12,27,31,35,39]. They felt uncomfortable in communicating with their adolescents on matters regarding sexuality [12,32,33,40].…”
Section: Involvement Of Parents In Sexuality Educationmentioning
confidence: 99%
“…The barriers that hindered parents in discussing sexuality matters were being examined in this review also. The parents reported that lack of knowledge [27,32,34,35,39]; lack of communicative skills [12,31]; adolescent know enough/ had learned about sexuality in school [12,33]; not parental role to provide sexuality education/responsible of school [12,28]; children are too young to know about sexuality [28]; and lack of motivation to discuss sexuality with their children [12].…”
Section: Involvement Of Parents In Sexuality Educationmentioning
confidence: 99%